Analysis of Accident Risk Points (Black Spots) on the Bubutan – Perak Barat Road Section Surabaya - Arsyi, Radyan Hafidz; Utomo, Nugroho; Solichin, Ibnu (CIVED, 2024)
According to the traffic accident data from the Traffic Accident Unit of the Tanjung Perak Port Police and the Traffic Accident Unit of the Dukuh Pakis Police in Surabaya City in 2020-2022, traffic accidents that occurred on the Bubutan Road - West Perak Road section experienced an increase in the number of traffic accidents. The total details in 2021 were 13 incidents, in 2022 there was an increase to 17 incidents, besides that, the material losses incurred in 2022 had the highest figure, which amounted to IDR 46,000,000. So it is necessary to analyze the accident-prone points on the road section. The method used are AEK (Accident Equivalent Number), IPA (Importance Performance Analysis) method, and calculation of free flow speed, traffic volume analysis, and side obstacle analysis. Based on the analysis of accident-prone areas using the AEK method, it is known that the upper control limit value is 36.07 where Jalan Perak Barat has an AEK value above the BKA value in 2021 of 37, then in 2022 of 40. Jalan Perak Barat has an average traffic volume of 434.47 smp / hour, with a moderate level of side obstacles, but has a free flow speed that exceeds the planned speed. One of the factors causing traffic accidents on Jalan Perak Barat is the driver of a vehicle traveling at high speed, so rumble strip planning and road facility rejuvenation are recommended.